2019
DOI: 10.1002/term.2882
|View full text |Cite
|
Sign up to set email alerts
|

Microparticles for controlled growth differentiation factor 6 delivery to direct adipose stem cell‐based nucleus pulposus regeneration

Abstract: Currently, there is no effective long‐term treatment for intervertebral disc (IVD) degeneration, making it an attractive candidate for regenerative therapies. Hydrogel delivery of adipose stem cells (ASCs) in combination with controlled release of bioactive molecules is a promising approach to halt IVD degeneration and promote regeneration. Growth differentiation factor 6 (GDF6) can induce ASC differentiation into anabolic nucleus pulposus (NP) cells and hence holds promise for IVD regeneration. Here, we optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…rhGDF6 significantly increased the expression of NP-marker genes (SOX9, ACAN, COL2A1, KRT8, KRT18, KRT19, FOXF1, CA12 and T) in NP cells and sGAG production following 14 days in culture. These results are similar to those observed for rhGDF6 stimulation of human MSCs [ 16 , 37 ] and provide further evidence of an anabolic role for GDF6 in healthy IVD homeostasis. rhGDF6 stimulation had no effect on the expression of catabolic enzymes (MMPs, ADAMTSs) in comparison to unstimulated controls, although levels were not induced in the system (e.g., through stimulation with a catabolic cytokine, such as IL-1β), hence GDF6 may not be able to reduce expression below basal levels and further work is required to interrogate this aspect in more detail.…”
Section: Discussionsupporting
confidence: 88%
“…rhGDF6 significantly increased the expression of NP-marker genes (SOX9, ACAN, COL2A1, KRT8, KRT18, KRT19, FOXF1, CA12 and T) in NP cells and sGAG production following 14 days in culture. These results are similar to those observed for rhGDF6 stimulation of human MSCs [ 16 , 37 ] and provide further evidence of an anabolic role for GDF6 in healthy IVD homeostasis. rhGDF6 stimulation had no effect on the expression of catabolic enzymes (MMPs, ADAMTSs) in comparison to unstimulated controls, although levels were not induced in the system (e.g., through stimulation with a catabolic cytokine, such as IL-1β), hence GDF6 may not be able to reduce expression below basal levels and further work is required to interrogate this aspect in more detail.…”
Section: Discussionsupporting
confidence: 88%
“…Firstly, they are inherently reliant upon the remaining degenerated disc cells to be healthy and sufficient in number to synthesize ECM and ultimately regenerate the disc tissue. Secondly, GF are often short-lived, limiting clinical use toward sustained regeneration [ 324 ]; hence, recent works were investigating the use of microparticles as a GF delivery vehicle [ 325 , 326 , 327 ]. Arguably, this is a likely contributing factor to the lack of efficacy from the GDF5 clinical trial.…”
Section: Ivd Regeneration Strategies: Biological Targets and Biomamentioning
confidence: 99%
“…Furthermore, controlled administration of biologicals is extremely valuable for IVD TE, where cell and/or growth factor therapeutics would rely on single surgical procedures rather than on repeated delivery. In vitro, delivery of GDF6 through MP was demonstrated to be more efficient than repeated exogenous delivery to differentiate adipose stem cells into NP cells [ 327 ], which provides a promising direction for single surgical procedure approaches. MP have also been used to release the anti-inflammatory factor cyclooxygenase-2 in a canine dog model of DD [ 438 ], leading to encouraging results of preventing disease progression and reducing the inflammatory signature prostaglandin E 2 , a crucial nociception mediator.…”
Section: Ivd Regeneration Strategies: Biological Targets and Biomamentioning
confidence: 99%
“…8,9 Work from our laboratory and others has demonstrated that stimulation of MSCs and ASCs with recombinant human (rh)GDF6 promotes their differentiation to an NP-like phenotype. 10-13 Furthermore, rhGDF6 induces greater increases in NP-marker genes and proteoglycan production than other candidate growth factors, namely rhGDF5 and rhTGFβ3, particularly in ASCs. 10…”
Section: Introductionmentioning
confidence: 99%